Design of Reliable Long-Distance Air-to-Ground Communication Systems Intended for Operation under Severe Multipath Propagation Disturbances - Otten, Klaus W. (I.R.E. transactions on aerospace and navigational electronics, 1962)
A survey of the principal methods of improving the reliability of long-range digital communication systems introduces the subject. Special modulation techniques as well as redundant transmission of pulses, redundant in time and in carrier frequency, are described as methods to counteract the effects of multipath distortion in connection with the proper special demodulation and diversity reception techniques. It is shown that for an air-to-ground communication system, in which Doppler shift has to be considered in addition to the multipath distortion, high reliability can be obtained if quantized frequency modulation (QFM) and time redundancy are properly applied. To make the protection against multipath distortion most effective, the transmitted signal must have a wide frequency band. The optimum time diversity requires interleaving the redundant pulses and, therefore, requires complex logic circuitry for its instrumentation. The design characteristics of an "optimum" air-to-ground long-range digital communication system are described. In the concluding section, it is indicated how one can apply the design principles for an "optimum" long-range communication system (as described) to the design of narrow bandwidth system with relatively simple instrumentation.